Unravelling the interplay between responsible leadership and public servants’ job performance: The role of affective organisational commitment - Son, Doan Bao; Thi Thu Hien, Pham; Nguyen Thanh Ha, Le (Journal of Finance - Marketing Research, 2025)
Public sector leadership improves employee performance and drives change. Job performance is the value of employee behaviours that support the organisation’s goals. By utilising social exchange theory, this study examines how and when responsible leadership affects public servants’ job performance in Vietnam, with person-organisation fit and affective organisational commitment serving as mediators and affective organisational commitment serving as a moderator. This work collected data from 329 Ho Chi Minh City public employees identified by convenience sampling. Structural equation modelling was used in both SPSS 26 and AMOS 24. This study found that responsible leadership boosts job performance. The results also show that person-organisation fit and affective organisational commitment partially mediate the relationship between responsible leadership and public servant job performance. Additionally, affective organisational commitment moderates the relationship between responsible leadership and job performance. According to the study, public organisations should have a rigorous leadership development program that encourages responsible leadership and improves employees’ job performance. The authors believe the present is one of the first studies to incorporate social exchange theory and examine the relationship between responsible leadership and job performance among Vietnamese public employees, considering affective organisational commitment as a mediating and moderating factor.